Interpretations and common challenges of aeolian records from North American dune fields. (29th July 2016) - Halfen, Alan F.; Lancaster, Nicholas; Wolfe, Stephen
Abstract: Geomorphic and chronologic data for dune fields are evaluated for three contrasting areas of North America: 1) the Prairie, Parkland and Boreal ecozones of the northern Great Plains in Canada; 2) the Central Great Plains of the USA; and 3) the deserts of southwestern USA and northern Mexico. Luminescence and radiocarbon ages for periods of dune accumulation and stability are compared with palaeoenvironment proxies to provide an assessment of the boundary conditions of dune system response to changes in sediment supply, availability, and mobility. Dune fields in the northern Great Plains were formed from sediment originating from glaciofluvial or glaciolacustrine sediments deposited during deglaciation 16–11 ka. Subsequent aeolian deposition occurred in Parkland and Prairie dune fields as a result of mid-Holocene (8–5 ka) and late-Holocene (<3.5 ka) activity related to drought conditions that reworked pre-existing aeolian sands. In the Central Great Plains, many dune fields are closely linked to fluvial sediment sources. Sediment supply was high during deglaciation of the Rocky Mountains and resulted in widespread dune construction 16–10 ka. Multiple periods of Holocene reactivation are recorded and reflect increased sediment availability during drought episodes. Dune fields in the southwestern deserts experienced periods of construction as a result of enhanced supply of sediment from fluvial and lacustrine sources during the period 11.8–8 ka and at intervals during the late Holocene centered on 1.5, 0.7, 0.4, 0.3, and 0.2 ka. Despite spatial and temporal gaps in chronometric data as a result of sampling biases, the record from North American dune fields indicates the strong influence of sediment supply on dune construction, with changes in sediment availability as a result of drought episodes resulting in dune field reactivation and reworking of pre-existing sediment.